Properties of Commutativity of Dual Toeplitz Operators on the Orthogonal Complement of Pluriharmonic Dirichlet Space over the Ball - Yinyin Hu; Yufeng Lu; Tao Yu (Journal of Function Spaces)
We completely characterize the pluriharmonic symbols for (semi)commuting dual Toeplitz operators on the orthogonal complement of the pluriharmonic Dirichlet space in Sobolev space of the unit ball. We show that, for f and g pluriharmonic functions, SfSg=SgSf on (Dh)⊥ if and only if f and g satisfy one of the following conditions: (1) both f and g are holomorphic; (2) both f¯ and g¯ are holomorphic; (3) there are constants α and β, both not being zero, such that αf+βg is constant.